Tingkat Pengetahuan Masyarakat Terhadap Swamedikasi Obat Bebas dan Obat Bebas Terbatas di Jl Bung Rt 003 Rw 001 Kelurahan Tamalanrea Jaya Kota Makassar - Murniati, Murniati; Agnes, Laupra (Politeknik Sandi Karsa, 2023)
Self-medication is the use of non-prescription medications by an individual on their own initiative. Self-medication with over-the-counter medicines and limited over-the-counter medicines can be risky if done continuously to treat diseases that do not go away. Self-medication requires knowledge before doing it so that there is no mistake in using the medicine, so this research aims to determine the level of public knowledge regarding the use of over-the-counter medicines and over-the-counter medicines for self-medication. held in April-May 2023 on Jl. Bung Rt 003 Rw 001 Tamalanrea Jaya Village, Tamalanrea District, Makassar City. This type of research uses a descriptive method, namely research that includes surveys with data collection in the form of questionnaires with a total of 79 respondents. The sampling technique uses a non-probability sampling technique, namely purposive sampling. The results of this research show that the percentage of respondents' answers is 91.45%. Based on these results, it can be concluded that the level of public knowledge regarding self-medication with over-the-counter drugs and over-the-counter drugs is included in the high category.